Nudging for Prompt Tax Penalty Payment: Evidence from a Field Experiment in Indonesia - Eko Arief Yogama; Daniel J. Gray; Matthew D. Rablen (Center for Economic Studies and ifo Institute (CESifo), 2023)
We conducted a randomised controlled trial in Indonesia to evaluate the effect of three intervention letters on tax penalty compliance behaviour. Over 10,000 individual taxpayers are randomly assigned to receive either a deterrence, information, or simplification letter, or no letter. Our results indicate that simplification, which makes paying a penalty less burdensome administratively by providing billing codes to pay the penalties, yields the highest probability of timely settlement, increasing compliance by 32 per cent compared to the control group. Deterrence also positively impacts penalty compliance, increasing timely settlement rates by 27 per cent. The least effective intervention is the information letter. Although associated with a 12 per cent increase in tax compliance, this effect is only statistically significant at the 10 per cent confidence level. Our results suggest that strategic messaging by tax authorities in developing countries can be a cost-effective tool for improving tax penalty payment compliance.
Keywords: C93; D91; H26; Z18; 330; tax penalties; tax compliance; RCT; simplification; deterrence; information; Indonesia